The usage of antibiotics in primary health care. - José Carles Zerquera; Grace A. de Lara García; Mariela García Gattorno; Rubén Rodríguez Rodríguez; Sorahy Santander García (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2008)
The usage of antibiotics is an important aspect in any doctor´s daily work. In primary health care this action requires a great relevance due to its common use. An updated bibliographical review and a search were performed with the aim to present the most frequent antibiotics used, the bases for its correct selection, time the treatment may last, as well as other information which are essential to be known by the medical personnel.